Impact of share repurchase announcement in Nordic indexes, Case: OMXH, OMXS & OMXC from 2013 to 2022 - Keko, Jussi (My University, 2026)
The objective of this study is to examine if long-term abnormal returns follow the share buyback announcements especially in the Nordic markets. Share buyback is relatively new form of payout policy but also seen as a substitution for more mature dividend policy. Investigation gathers information how capital structure and payout policy incorporate into the price changes over two year horizon. Theoretical framework is primarily focusing on efficient market hypothesis but also giving perspective on how signalling theory and information asymmetry might play crucial role when management is doing decisions payout policies. Additionally, multiple key financial figures are utilized to confirm how optimal capital structure and agency costs is built to obtain excess returns from the Nordic indexes. The empirical analysis explores leading indexes in Nordic markets from Finland, Sweden and Denmark (OMXH25, OMXS30 and OMXC25). Empirical analysis is using sample of 167 from the firms listed in the Nordic indexes. The methodology is focusing on Buy and hold abnormal returns to explain the long-term performance of the corporates announcing the share buyback policies over one-year and two-year horizons. Furthermore, multiregression analysis gives a deeper understanding on whether optimal capital structure or different aspects such as free cash flow or liquidity ratios explains the abnormal returns. Results from the empirical analysis suggest that there is some statistical significance after the companies announce the share buybacks over the two-year horizon and the abnormal returns, where median reaching 5.97 percent. Firms that are included in the study are all included in the leading index on the respective Nordic markets and are required to announce these changes publicly to all the investors. Therefore, the results are challenging the semi-strong form of market efficiency. Additionally, country-specific observations deliver more profound aspect how even in the relatively homogenous markets are still behaving differently over a two-year period.
Keywords: shares; dividends; enterprises; efficiency (properties); markets (systems); security market; prices; repurchases; investors; Nordic countries; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance